Эффективность теплоутилизаторов стекловаренных печей в условиях запыленности поверхностей нагрева - Фиалко, Н. М.; Степанова, А. И.; Навродская, Р. А. (Енергетика і автоматика, 2017)
EFFICIENCY HEAT EXCHANGER GLASS FURNACES IN DUSTY CONDITIONS OF HEATING SURFACES. N. Fialko, А. Stepanovа, R. Navrodskaya An integral part of the general problem of economic stability in Ukraine is the effective functioning of the economy through the sustainable provision of all types of production of fuel and energy resources. One of the important factors of economy of energy and material resources is the utilization of the heat of the flue gases of power plants, which would greatly offset the needs of enterprises in the heat, the production of which is now spent more energy resources. At various purposes plants recycle waste heat is associated with certain difficulties, due to the presence of flue gases in a significant amount of contaminating component content ranges from 50 to 1000 mg / m3. These components include sand, sodium, aluminum, carbon black, and the corrosive compounds of nitrogen, sulfur, carbon, fluorine and other harmful or chemically aggressive substances in the gaseous phase. The solid components in the flue gas to cause the formation of heat exchanger heat transfer surfaces included in the heat recovery system, the slag deposit layer. In conditions of high dust content of exhaust gases of glass furnaces quickly forms on the heat exchange surfaces heat exchanger layer of sediments is an obstacle to the effective use of advanced heat transfer surfaces, including finned tubes, since the complex configuration of the heat exchange surface of the removal of polluting by-layer is extremely difficult. In this case, the operation of the exchanger takes place if sediment layer, resulting in a significant reduction in the effectiveness of the heat exchanger and ultimately to the loss of efficiency. In this paper, based on analysis of the efficiency of the heat exchanger air tube glass furnace operating conditions of dust heating surfaces, suggested criteria for assessing the maximum permissible degree of contamination of heat exchange surfaces and calculated the recommended timing of their treatment. To determine the criteria for evaluating the maximum permissible degree of pollution, the heat exchange surface of the heat exchanger air tube glass furnace conducted research on the effectiveness of this heat exchanger, depending on the pollution factor. For gas-air heat recovery units derived functional relationship Exergy Technology efficiency criterion from the main operating and structural parameters of the heat exchanger. With the help of this dependence is calculated based Exergy Technology endpoint of pollution coefficient of the tube bundle heat exchanger. Based on these studies suggested evaluation criteria for the maximum permissible degree of contamination of the heat transfer surfaces and heat recovery units designed the recommended timing of their treatment.